Dukungan Sosial Orangtua Terhadap Anak Dalam Belajar Ditinjau dari Tingkat Pendidikan Orangtua - Martina Winarni (LPPM Universitas Proklamasi 45, 2005)
Should children pursue their education especially when parents need their children's assistance desperately in farming? It is more likely parents prefer them working to studying. Parents also perceive that there is no guarantee for being employed for their children with high educational level. These narrow perceptions are undoubtedly come from their limited educational level. One hundred and forty eight students from the SMANII Playen Gunung Kidul, Grade 2, participate enthusiastically on this research. The research hypothesis presumes that there is a positive correlation between the parent's educational level and parent's social support for their children in pursuing study. The higher parent's educational level, the stronger their social support. Research's result indicates that the hypothesis is significant (r = 0.172, p<0.05). The determinant coefficient is only 0.029584. It means that the prediction of parent's social support by the educational level is only 2.9% or 3%. Other variables which do not include on this research contribute 97% on explaining the emerging of social support.